Comparative Study of Novel Phosphordiamidite and Phosphite Ligands Used in Alkene Hydroformylation; Synthesis, Characterization, Metalation, and Catalytic Evaluation. Issue 37 (27th September 2018) - Hastings, Samantha D.; Cagle, Ethan C.; Totsch, Timothy R.; Tyus, Shakyra D.; Gray, Gary M.
Abstract : Three novel ligands have been prepared by the reactions of 1, 1′‐(chlorophosphinediyl)bis(1 H ‐pyrrole) with either 2‐pyridinemethanol or 2, 6‐pyridinedimethanol or the reaction of 1, 1′‐biphenyl‐2, 2′‐diyl phosphorochloridite with 2‐pyridinemethanol. Measurement of | 1 J P–Se | values demonstrate that the phosphite donor is less basic than the phosphoramidite donors. Coordination preferences of the ligands in octahedral cis ‐tetracarbonylmolybdenum(0) and square planar cis ‐dichloropalladium(II) complexes have been evaluated using multinuclear NMR and X‐ray crystallography. Rhodium(I) complexes of the bidentate ligands have been evaluated as catalysts for styrene hydroformylation, and their activities are nearly double those of catalysts containing traditional phosphites. The regioselectivities of the Rh I complexes of the bidentate ligands are not significantly different at 80 °C and 20 atm and are not affected by the addition of a lithium salt. In contrast, changing reaction conditions causes the % n ‐aldehyde to vary from 15 to 50 %. The regioselectivity of the catalyst containing the bidentate phosphoramidite/pyridine ligand was more sensitive to pressure than temperature with both effects being significant. Abstract : Three novel phosphordiamidite and phosphite ligands have been synthesized and characterized. Evaluations of the σ‐donating abilities of the ligands indicate that the phosphite ligand is more basic than the phosphoramidite analogs. Model complexes of the ligands have been prepared to study coordination preferences with octahedral and square planar centers and these have been characterized by multinuclear NMR and X‐ray crystallography.